PSYCHOLOGICAL ASPECTS OF THE PROFESSIONAL WORK PERFORMED BY POLICE OFFICERS FROM THE RESPONSE UNITS OF THE SECURITY POLICE - Ostapovych, Volodymyr; Barko, Vadym; Moiseieva, Olena (PSYCHOLOGICAL JOURNAL, 2020)
The article defines and generalizes the psychological aspects of professional work performed by police officers form the response units of the security police. On the basis of wide experiment involving 300 police officers from 20 regions of Ukraine, the individual professionally important qualities of police officers were defined. The profession of response unit police officers of the security police places certain requirements on their psychomotor characteristics and their sensory-perceptual abilities. They should have a sufficient level of functional brain activity, a developed vestibular apparatus, and a sufficiently high rate of simple reactions and reactions to a moving object. Police officers also need to have developed cognitive processes (attention, memory, thinking) and speech skills. The profession of response unit police officers of the security police force sets certain requirements for the unit employees’ general and special professional abilities (high and medium levels of verbal intelligence, higher than average speed of divergent thinking, formed mental operations of analysis and synthesis, induction and deduction, abstraction). The police officers must be able to persuade, influence an interlocutor, be responsible for their actions and orders, give an objective assessment of their own actions and actions of others, optimally combine business and personal contacts, attract attention and interest of people, and arouse their feelings of trust. Organizational and special capabilities are also significant for the professional work of response unit police officers of the security police. The performed empirical study revealed a list of necessary professional qualities that response unit police officers of the security police must possess: strong or medium-strong types of the nervous system, high or average levels of general abilities, highly developed special professional abilities, high or average communicative abilities, high psychomotor skills, corresponding character traits and emotional-volitional qualities, sufficiently developed cognitive processes.